Hukum Memberikan Rating dan Informasi yang Tidak Benar Perspektif Fatwa MUI No 24 Tahun 2017 pada Online Shop di Kota Medan - Mutia Khalisah; Fatimah Zahara (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to comprehend the legal aspects related to providing inaccurate ratings and data according to the Fatwa MUI No. 24 of 2017 concerning online stores in the city of Medan. Several online business platforms like Shopi, Lazada, and Tokopedia offer rating and survey features visible to buyers. These ratings, usually represented by stars, and surveys reflect views or analyses of the service provided by the merchants. However, the presence of this evaluation feature can be detrimental to businesses if buyers give ratings and surveys that do not align with facts and lack clear reasons, even though the businesses have genuinely provided good customer service. The focus of this research is to analyze the legal aspects regarding the provision of inaccurate ratings and data that harm businesses, referring to the Fatwa MUI No. 24 of 2017 about online stores in the city of Medan. This study employs an exact juridical approach with an exploratory examination strategy that emphasizes valid investigation. The Fatwa explicitly highlights prohibited activities in web-based communication and entertainment for the Islamic community, including fraudulent actions, defamation, mutual insults, and threats.